THE PENTAHELIX MODEL IN SYNERGIZING SECTORS TOURISM IN WEST JAVA TO IMPROVE LOCAL ECONOMY - Sukmadi Sukmadi (Bajang Institute, 2022)
West Java Province is a large province with various Regencies and Cities with a strategic location in its economic activities, especially in tourism. The development of tourism in West Java will provide a positive value to the growth in the number of both domestic and foreign tourists visiting West Java. One of the strategies launched by the government in tourism development is through the use of the Pentahelix Model. Pentahelix has an important role to play in supporting shared innovation goals and pentahelix contributing to regional socio-economic progress. Based on the discussion that has been concluded, it can be concluded that the Culture and Tourism Office in West Java should carry out optimal planning in managing and developing tourist objects by creating a sustainable program, making short, medium and long term targets as guidelines or benchmarks for targets to be achieved. The mobilizing function carried out by the Disbudpar does not only form coordination activities in the field of monitoring potential tourist objects, available facilities and infrastructure but also focuses dominantly on empowering existing human resources in potential villages/regions in West Java by providing various coaching and training, inviting experts to impart special knowledge to the public. The Provincial Government through Disbudpar must be more creative in getting support, must be more able to make them interested and must further enhance collaboration with the 5 stakeholders based on the pentahelix model, so that all aspects involved in parwiata activities can synergize with each other to achieve improvement and development of the local economy.